Colour improvement of common carp (Cyprinus carpio) fillets by hydrogen peroxide for surimi production - Seyed Jafarpour Khozaghi; Farrokh Sherkat; Brian Leonard; Elisabeth Gorczyca (2008)
The preferred colour for surimi is white, but surimi prepared from light fillets of common carp (Cyprinus carpio) is slightly pink. Hydrogen peroxide (H2O2; 1-3% v/v) with and without sodium tri-polyphosphate (STP; 1-2% w/v) was added to a sodium carbonate bath (pH 7.0-11.5) resulting in a final pH range of 4.4-10.1 which was injected into carp fillets. After soaking and tumbling for 30 min at 4-10 °C, the fillets were evaluated for colour and water holding capacity (WHC). Fillets tumbled with treatment solution with different pH levels (7.0-11.5), but with no H2O2 or STP added, had improved colour with significantly (P < 0.05) higher L* compared with untreated fillets as the control. However, the colour improvement [(L* and colour deviation (?E)] was not significantly different (P > 0.05) within the pH levels (7.0-11.5) trialled. With increasing H2O2 levels (1-3%), fillets became lighter and ?E increased significantly (P < 0.05), especially with a 3% H2O2 treatment at pH of 10.5 (adjusted pH before H2O2 addition, actual pH after H2O2 addition was 8.2). The whiteness (L*-3b*) of kamaboko produced from treated (3% H2O2, pH 10.5) common carp light fillets was not significantly different to that of kamaboko from Alaska pollock and threadfin bream. Treatments combining H2O2 (3%) with STP (1-2%) significantly reduced the L* value obtained in comparison with fillets treated with only H2O2 (3%). Similarly, fillets treated with STP (1%) alone, resulting in lower L* values, irrespective of treatment pH (7.0-11.5). WHC, an indicator of the quality of the fillet texture, increased from 816 g/kg at pH 7.0 without STP to 841 g/kg at pH 11.5 with 1% STP. Treatment with H2O2 (without STP) decreased the WHC of the fillets.